2008
DOI: 10.1002/uog.6288
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic determination of the position of a levonorgestrel intrauterine device

Abstract: ) is not echogenic and may be more difficult to see on ultrasound imaging. Although the vertical stem of the LNG-IUD is not clearly visible, in a sagittal section of the uterus it creates an acoustic shadow of about 2 cm between the echogenic proximal and distal ends of the stem and is seen to extend from above the isthmus to the fundus (Figure 1). Both arms of the crossbars are slightly echogenic and usually visible in a transverse section (Figure 2). The strings hanging at the proximal end are echogenic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Factors previously reported to be associated with malpositioning of IUDs include inexperience of the health professional, insertion of the device within the first 6 months after delivery, nulliparity, a retroflexed uterus, and previous cesarean deliveries . In our study, the use of 3D US confirmed that in all of our participants, the LNG‐IUD was entirely located inside the uterine cavity, but in eight of these women, the device was not aligned with the main axes of the uterus.…”
Section: Discussionsupporting
confidence: 77%
“…Factors previously reported to be associated with malpositioning of IUDs include inexperience of the health professional, insertion of the device within the first 6 months after delivery, nulliparity, a retroflexed uterus, and previous cesarean deliveries . In our study, the use of 3D US confirmed that in all of our participants, the LNG‐IUD was entirely located inside the uterine cavity, but in eight of these women, the device was not aligned with the main axes of the uterus.…”
Section: Discussionsupporting
confidence: 77%
“…However, compared with copper IUDs, the LNG IUS is more likely to be missed by ultrasonography. LNG IUS is compounded with barium sulfate, which makes it radio opaque for X-ray recognition [ 14 ]. A plain X-ray can therefore be used as an adjunctive imaging modality in the case of a lost LNG IUS not seen on ultrasound [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that copper IUDs are easier to visualise with ultrasound, whereas imaging of Mirena IUDs is not as accurate and requires higher operator skill. 6,14,15 All of the indeterminately positioned IUDs shown in Figure 2 were Mirena IUDs and were inadequately visualised due to poor echogenicity and partial views of the device. Valsky et al 16 found that the IUD acoustic shadow on the 3D-reconstructed coronal image can give a good clue to its location.…”
Section: Discussionmentioning
confidence: 99%